Overexpression of estrogen receptor-α in human papillary thyroid carcinomas studied by laser-capture microdissection and molecular biology - Di Vito, Maura; De Santis, Elena; Perrone, Giulietta Anna; Mari, Emanuela; Giordano, Maria Chiara; De Antoni, Enrico; Coppola, Luigi; Fadda, Guido; Tafani, Marco; Carpi, Angelo; Russo, Matteo A. (Cancer science, 2011)
The expression pattern of estrogen receptor (ER) isoforms in normal and tumor thyroid tissues is still controversial and poor defined, therefore, a more detailed study of the distribution of these molecules is needed. Most discrepancies might be due to the methods utilized. We studied the expression of ER isoforms in human papillary thyroid carcinoma (PTC), in fine‐needle aspiration biopsy‐derived specimens, and in cells, using more accurate techniques, such as laser‐capture microdissection, real‐time quantitative PCR, and Western blot. Laser‐capture microdissection allowed us to isolate homogeneous cell populations from human PTC surgical samples. Tumor, peritumor, or normal host tissue of the same sample were separately dissected and analyzed by RT‐PCR and Western blot. Estrogen receptor‐α mRNA was more expressed in cancer‐microdissected cells from human PTC, as compared with microdissected cells obtained from surrounding normal host tissue (450 vs 12, P = 0.001). A similar pattern was observed with Western blot for the ER‐α protein. By contrast, ER‐β mRNA expression was not detected among the microdissected tissue fractions. Fine‐needle aspiration biopsy‐derived specimens showed a similar expression pattern to ER. Moreover, human PTC cell line BCPAP and cancer stem cells from PTC, analyzed under hypoxic conditions, showed a hypoxia‐driven increase in ER‐α expression. In conclusion, ER‐α might have an important role in human PTC, and its overexpression can be studied in routine needle aspirate as a possible marker of malignancy. (Cancer Sci 2011; 102: 1921–1927)